PERSPECTIVES OF USING ARTIFICIAL INTELLIGENCE IN POSTGRADUATE MEDICAL EDUCATION - Пашковський, Валерій; Пашковська, Наталія; Царик, Ірина (SWorldJournal, 2023)
The field of postgraduate medical education is continuously evolving, with advancements in technology playing a significant role in shaping its future. One such advancement is the integration of artificial intelligence (AI) or piece intelligence (PI) into